Fairness in International Trade Policy: Equality and Differential Treatment in Theory and Practice - Johann Jakob Häußermann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In 'Fairness in Practice – A Social Contract for a Global Economy' (2012) Aaron James proposes a substantial normative framework for a theory of fairness in the global economy. Based on a distinctive methodology of interpretive constructivism, James argues for an internal justification of fairness requirements in the field of international trade, and consequently defends three basic egalitarian principles of fairness. However, Mathias Risse and Gabriel Wollner, among others, have criticized James's view for multiple reasons. In the following article, I will first engage with their critique, contending that their arguments do not prove that James's view should be dismissed. Instead, I will introduce a new proposal, arguing that it is rather by a notion of differential treatment of countries that James's account should be complemented. Taking into account all the relevant differences between countries, the concept of differential treatment allows for the provision and establishment of equal participation as a basis for considerations of fairness. To this end, I shall therefore propose an additional fourth principle of fairness called Equal Participation. I argue that it is necessary to significantly expand James's contractualist and practice-dependent foundations, in order to reconcile crucial methodological concerns and to render James's formulations applicable to current debates on free trade agreements. The article will conclude with an exploration of the applicability of this new approach to current trade policy issues, illustrating not only its practicability but also the urgent need for normative considerations in the context of international trade agreements.
Keywords: D63; F13; 330; International Trade; Free Trade Agreements; Fairness; Special and Differential Treatment; Constructivism; Aaron James